The Institutional Governance of Plantation Supply Chains under Ngawi's Downstreaming Policy - Ratu Zahra; Ahmad Zaki Fadlur Rohman (University of Merdeka Malang, 2026)
Ngawi Regency embodies a paradox of primary-sector abundance: on the slopes of Mount Lawu, output of coffee, cocoa, and clove keeps climbing, yet manufacturing contributes only 10.12% of Gross Regional Domestic Product while most of the harvest leaves the district in raw form. This study explains why an abundant upstream supply fails to spark local processing, and identifies the institutional reconfiguration needed for value added to be captured locally. Working within a qualitative, descriptive embedded case study, we read the supply chains through Elinor Ostrom's Institutional Analysis and Development framework, triangulating a documentary analysis of the Thematic Bureaucratic Reform Action Plan on Downstreaming and sectoral statistics against in-depth interviews with key informants. Value-added leakage is not a natural market anomaly; it is what dysfunctional rules-in-use produce. Weak boundary and aggregation rules keep collective economic institutions from forming; information rules are choked by the lack of an integrated upstream–downstream database; and payoff rules stay lopsided because long-term supply contracts are absent. The going practice individual, standing-crop sales, the tebasan system settles into a suboptimal equilibrium that pins farmers to a weak bargaining position. Downstreaming can succeed only through a simultaneous reconfiguration of the rules-in-use spatial clustering, stronger village-level aggregator institutions, an integrated value-chain information system, and aligned cross-agency performance indicators making it, in essence, a task of institutional engineering rather than one of mere equipment provision.